Traditional fermented foods, indigenous knowledge systems, and gut microbiome health among tribal communities of Tripura, India: an integrative review - Manabendra Debnath (Journal of Ethnic Foods, 2026)
Abstract Tripura, a biodiversity-rich state in Northeast India, is home to nineteen officially recognised tribal communities whose food cultures encompass a diverse array of traditionally fermented foods (TFFs). These preparations—including Chuak (fermented rice beer), Mui Borok (fermented bamboo shoot), Berma (fermented fish), and Saraieng (fermented mustard leaf), among others—represent the convergence of millennia-old indigenous knowledge, ecological expertise, and empirically validated nutritional wisdom. Despite their deep cultural embeddedness and role in community health maintenance, they have received limited systematic scientific attention, particularly regarding gut microbiome-modulating properties. This integrative review synthesises evidence from ethnomicrobiology, food science, nutritional biochemistry, and gut microbiome research to examine: the catalogue and characterisation of major TFFs across Tripura's tribal communities; the microbial ecology of these preparations and its correspondence with known probiotic genera; mechanisms through which TFF consumption may modulate gut microbiome composition and function; indigenous knowledge transmission pathways and erosion risk; and the nutritional and bioactive profiles of selected TFFs. Findings indicate that Tripura’s TFFs harbour diverse lactic acid bacteria—particularly Lactobacillus plantarum, L. fermentum, Leuconostoc mesenteroides, and Pediococcus pentosaceus—alongside Bacillus-mediated alkaline ferments. These organisms produce bacteriocins, short-chain fatty acids, bioactive peptides, and B-vitamins that collectively exert beneficial effects on gut barrier integrity, immune modulation, and pathogen exclusion. The review identifies critical research gaps and calls for urgent community-participatory documentation, biobank development, and Geographical Indication protection of Tripura’s fermentation microbiome heritage.